Answer:
If spongebob recieved 4 candies for every 2 that Patrick Got then bob got 16 and patrick got 8.
Step-by-step explanation:
Use the Pythagorean Theorem to find the missing lengths<span> of the </span>sides<span> of a right triangle. triangle that has an opposite </span>side<span> of </span>length 3<span> and a hypotenuse of </span>length<span> 4. </span>Determining<span> all of the </span>side lengths<span>and angle measures of a right triangle is Let's look at how to do this when you're given </span>one side length<span>and </span>one<span> acute</span>
Answer:
![f(g(x))=f\left(-\dfrac{3x+21}{5}\right)=x\\\\g(f(x))=g\left(-\dfrac{5}{3}x-7\right)=x](https://tex.z-dn.net/?f=f%28g%28x%29%29%3Df%5Cleft%28-%5Cdfrac%7B3x%2B21%7D%7B5%7D%5Cright%29%3Dx%5C%5C%5C%5Cg%28f%28x%29%29%3Dg%5Cleft%28-%5Cdfrac%7B5%7D%7B3%7Dx-7%5Cright%29%3Dx)
Step-by-step explanation:
Fill in the given expressions and simplify.
![f(g(x))=f\left(-\dfrac{3x+21}{5}\right)=-\dfrac{5}{3}\left(-\dfrac{3x+21}{5}\right)-7\\\\=\left(-\dfrac{5}{3}\right)\left(-\dfrac{3x}{5}\right)-\left(\dfrac{5}{3}\right)\left(-\dfrac{21}{5}\right)-7\\\\=\dfrac{15x}{15}+\dfrac{5\cdot 21}{3\cdot 5}-7=x+7-7=x](https://tex.z-dn.net/?f=f%28g%28x%29%29%3Df%5Cleft%28-%5Cdfrac%7B3x%2B21%7D%7B5%7D%5Cright%29%3D-%5Cdfrac%7B5%7D%7B3%7D%5Cleft%28-%5Cdfrac%7B3x%2B21%7D%7B5%7D%5Cright%29-7%5C%5C%5C%5C%3D%5Cleft%28-%5Cdfrac%7B5%7D%7B3%7D%5Cright%29%5Cleft%28-%5Cdfrac%7B3x%7D%7B5%7D%5Cright%29-%5Cleft%28%5Cdfrac%7B5%7D%7B3%7D%5Cright%29%5Cleft%28-%5Cdfrac%7B21%7D%7B5%7D%5Cright%29-7%5C%5C%5C%5C%3D%5Cdfrac%7B15x%7D%7B15%7D%2B%5Cdfrac%7B5%5Ccdot%2021%7D%7B3%5Ccdot%205%7D-7%3Dx%2B7-7%3Dx)
Going the other way, we have ...
![g(f(x))=\displaystyle -\frac{3\left(-\frac{5}{3}x-7\right)+21}{5}=-\frac{-5x-21+21}{5}=x](https://tex.z-dn.net/?f=g%28f%28x%29%29%3D%5Cdisplaystyle%20-%5Cfrac%7B3%5Cleft%28-%5Cfrac%7B5%7D%7B3%7Dx-7%5Cright%29%2B21%7D%7B5%7D%3D-%5Cfrac%7B-5x-21%2B21%7D%7B5%7D%3Dx)
Answer:
Parallelogram
Step-by-step explanation:
Hope this helps! Please leave any questions or concerns in the comments, byeee <3
Answer:
I cannot view the picture so I will tell you the formula
Step-by-step explanation:
Multiply the base by the height and divide the product by two.